Approaches to the Determination of the Working Area of Parallel Robots and the Analysis of Their Geometric Characteristics - MALYSHEV, Dmitry; POSYPKIN, Mikhail; RYBAK, Larisa; USOV, Alexander (Engineering Transactions, 2019)
The article presents and experimentally confirms two approaches to the problem of determining the working area of parallel robots using the example of a planar robot DexTAR with two degrees of freedom. The proposed approaches are based on the use of constraint equations of coordinates. In the first approach, the original kinematic equations of coordinates in the six-dimensional space (two coordinates describing the position of the output link and four coordinates – the rotation angles of the rods) followed by projecting the solution onto the two-dimensional plane is used. In the second approach, the system of constraint equations is reduced to a system of inequalities describing the coordinates of the output link of the robot, which are solved in a two-dimensional Euclidean space. The results of the computational experiments are given. As an algorithmic basis of the proposed approaches, the method of non-uniform coverings is used, which obtains the external and internal approximation of the solution set of equality/inequality systems with a given accuracy. The approximation is a set of boxes. It is shown that in the first approach, it is more efficient to apply interval estimates that coincide with the extremes of the function on the box, and in the second approach, grid approximation performs better due to multiple occurrences of variables in inequalities.